2023
DOI: 10.1111/bph.16019
|View full text |Cite
|
Sign up to set email alerts
|

Functional crosstalk between angiotensin receptors (types 1 and 2) and relaxin family peptide receptor 1 (RXFP1): Implications for the therapeutic targeting of fibrosis

Abstract: Class A, rhodopsin‐like, G‐protein‐coupled receptors (GPCRs) are by far the largest class of GPCRs and are integral membrane proteins used by various cells to convert extracellular signals into intracellular responses. Initially, class A GPCRs were believed to function as monomers, but a growing body of evidence has emerged to suggest that these receptors can function as homodimers and heterodimers and can undergo functional crosstalk to influence the actions of agonists or antagonists acting at each receptor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 159 publications
(299 reference statements)
0
0
0
Order By: Relevance
“…Relaxin (RLX) is a hormone with antifibrotic properties that inhibits profibrotic cytokine-mediated abnormal fibroblast proliferation, differentiation and matrix production by binding to its primary receptor RXFP1 (relaxin family peptide receptor 1) (Zhou et al 2021b ; Samuel et al 2022 ). Previous research have demonstrated that RLX has the ability to upregulate matrix metalloproteinase (MMP), including MMP-2 and MMP-9, and decrease the formation of fibrotic ECM in the treatment of pancreatic cancer and prostate cancer, resulting in positive therapeutic outcomes (Mardhian et al 2018 ; Feng et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Relaxin (RLX) is a hormone with antifibrotic properties that inhibits profibrotic cytokine-mediated abnormal fibroblast proliferation, differentiation and matrix production by binding to its primary receptor RXFP1 (relaxin family peptide receptor 1) (Zhou et al 2021b ; Samuel et al 2022 ). Previous research have demonstrated that RLX has the ability to upregulate matrix metalloproteinase (MMP), including MMP-2 and MMP-9, and decrease the formation of fibrotic ECM in the treatment of pancreatic cancer and prostate cancer, resulting in positive therapeutic outcomes (Mardhian et al 2018 ; Feng et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…While angiotensin II type 1 (AT 1 ) and type 2 (AT 2 ) and relaxin RXFP1 receptors have long been associated with disease progression, there has been little focus on the interplay and functional cross‐talk between these receptors in myofibroblasts. Samuel et al (2024) detail the profibrotic and antifibrotic properties of each receptor, including progress with clinical trials for an AT 2 receptor agonist. They then explore the therapeutic implications for receptor cross‐talk in fibrosis, using the example of reduced efficacy of targeting AT 2 or RXFP 1 when co‐administered with an AT 1 receptor blocker.…”
mentioning
confidence: 99%